A novel tension-based controller design for the quadrotor–load system. (July 2021) - Sun, Liang; Wang, Kaixuan; Mishamandani, Amir Hossein Alikhah; Zhao, Guowei; Huang, Hai; Zhao, Xurui; Zhang, Bin
Abstract: The problem of balancing a quadrotor with a suspended load in hovering and level flights has been achieved by using different linear and nonlinear control approaches. However, to the best of our knowledge, this problem has not been solved by using tension-based attitude tracking control. In this paper, a novel solution to the tension-based controller design for the quadrotor–load system has been demonstrated. Even more, pendular characteristics of the quadrotor with suspended load have been fully analyzed for the first time. Based on the results of the above-mentioned analysis and applying it to the proposed model, the expected attitude trajectory not only ensures the flight safety, but also reduces the energy consumption of the controller. Compared with existing control methods, this method provides the desired tension by a windlass mechanism which is mounted on the quadrotor. By employing the terminal sliding surfaces in a hierarchical way and performing the Lyapunov stability analysis, it has been shown that the tracking error in finite time converges to zero. Finally, a numerical simulation has been performed to demonstrate the effectiveness of the proposed scheme.